Primary Mast Cell Tumor in the Palpebral Conjunctiva in a Dog - Bonamigo, Renata; Bonfada Lang, Francisca; de Oliveira, Augusto; Uchoa Soares, Ana Bárbara; Nomi Hirata, Vinicius; Melazzo de Andrade, Cinthia; Martins Flores, Mariana; Krause, Alexandre (Acta Scientiae Veterinariae, 2024)
Background: Mastocytoma is the neoplastic proliferation of mast cells. This neoplasia exhibits a mild to extremely aggressive biological behaviour and can develop in any anatomical location. It is considered one of the most clinically relevant oncodermatological disorders in veterinary medicine, although it is considered rare in the conjunctiva of dogs. The objective of this work is to describe the case and highlight the importance of cytological examination in the diagnosis and treatment. Case: A 13-year-old mixed-breed neutered dog was brought to the Veterinary Teaching Hospital for presenting a nodule in the lower palpebral conjunctiva of the right eye for the past 3 months. The patient had good body condition and was clinically healthy. At the ophthalmic examination, a nodular and whitish enlargement with a smooth surface was observed on the lower palpebral conjunctiva of the right eye. No impairment of vision or ocular reflexes or any other alterations in the left eye were noted. Material obtained from the lesion with swab for cytological examination and stained with Diff Quick and allowed to obtain the diagnosis of mastocytoma. The cellularity was low to moderate and composed of round cells. The cytoplasm appeared indistinct with numerous metachromatic granules. The nucleus was rounded, paracentral, with condensed chromatin and inconspicuous nucleoli. Moderate anisocytosis and anisokaryosis were also observed. Complete blood count and serum biochemistry results were performed, and the results obtained were within reference values. The treatment consisted of surgical excision of the nodule with a margin of 0.5 mm on all edges followed by compressive hemostasis. The material obtained by the surgical excision was sent for histopathological analysis to confirm the cytological diagnosis and for surgical margin delimitation. On macroscopy, two eyelid fragments were identified. The tissue was firm and uniformly whitish. The smaller fragment was irregular and whitish. Microscopically, in the palpebral conjunctiva, beneath the surface epithelium, a non-circumscribed, non-encapsulated, and densely cellular infiltrative neoplastic proliferation was observed. The cells were round, with moderate amount of cytoplasm, a large number of intracytoplasmic basophilic granules, and well-defined cytoplasmic borders. The nuclei were round, with condensed chromatin and inconspicuous nucleoli. Cellular and nuclear pleomorphism was classified as moderate, and, after evaluation 10 fields at a magnification of 400x, no mitoses were seen. Toluidine blue staining improved the observation of cytoplasmic granules. Additionally, a multifocal and pronounced inflammatory infiltrate of eosinophils was noted. Histopathology findings confirmed the cytological diagnosis of mastocytoma. The patient showed good recovery after the surgical procedure with no local recurrence of the tumor after 60 days. Discussion: In clinical routine, to obtain an adequate sample for diagnosis is not always easy. The less traumatic and invasive technique should be preferred to minimize complications related to physical or chemical restraint. The time to obtain diagnostic information is also crucial for the treatment outcome. Cytological examination of a specimen obtained by swab and stained with Diff Quick staining proved to be effective for the diagnosis of a mastocytoma in the palpebral conjunctiva, a very unusual site of this tumor, demonstrating the relevance of this technique. Keywords: mast cells, cytology, histopathology, dog, oncology.